2022
DOI: 10.2147/cia.s382912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcutaneous Acupoint Electrical Stimulation on Urinary Retention and Urinary ATP in Elderly Patients After Laparoscopic Cholecystectomy: A Prospective, Randomized, Controlled Clinical Trial

Abstract: Purpose To investigate the effect of transcutaneous electrical acupoint stimulation (TEAS) on urinary retention after laparoscopic cholecystectomy in elderly patients, and to explore the relationship between TEAS and urinary ATP. Patients and Methods The TEAS group was administered active TEAS at specific acupuncture points prior to induction of anesthesia and continued for 45 mins after surgery. In the control group, participants received sham stimulus at the same acup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A total of 1432 participants were analyzed in these RCTs, with 715 in the TEAS group and 717 in the control group. The surgery types of three studies were abdominal surgery, 17 , 25 , 28 five studies were spinal surgery, 18 , 20 , 23 , 26 , 27 three studies were orthopedic surgery, 21 , 22 , 24 and one study was cardiac surgery. 19 In the included studies, POD was assessed by the Richmond Agitation-Sedation Scale (RASS), CAM, and their variants differed at postoperative first day to seventh day, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 1432 participants were analyzed in these RCTs, with 715 in the TEAS group and 717 in the control group. The surgery types of three studies were abdominal surgery, 17 , 25 , 28 five studies were spinal surgery, 18 , 20 , 23 , 26 , 27 three studies were orthopedic surgery, 21 , 22 , 24 and one study was cardiac surgery. 19 In the included studies, POD was assessed by the Richmond Agitation-Sedation Scale (RASS), CAM, and their variants differed at postoperative first day to seventh day, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Most biases were concentrated on selection bias, performance bias, and detection bias. Except for three studies that were evaluated as having low bias, 23 , 25 , 27 the other studies were identified as uncertain based on the risk of bias. 17–22 , 24 , 26 , 28 Besides, three studies 19 , 23 , 27 had a high risk of reporting bias due to the presence of some outcome indicators without analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations